2019
DOI: 10.1016/j.icarus.2019.05.030
|View full text |Cite
|
Sign up to set email alerts
|

A common origin for dynamically associated near-Earth asteroid pairs

Abstract: identified and studied for over a decade, very few pair systems have been identified in the near-Earth asteroid population. We present data and analysis that supports the existence of two genetically related pairs in near-Earth space. The members of the individual systems, 2015 EE7 -2015 FP124 and 2017 SN16 -2018 RY7, are found to be of the same spectral taxonomic class, and both pairs are interpreted to have volatile-poor compositions. In conjunction with dynamical arguments, this suggests that these two syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…However, certain ancillary evidence supports the common origin scenario for this cluster, such as, highly similar spectra suggesting rare B-type taxonomic classifications for the two largest members of the cluster and the almost identical polarization properties of their surfaces (Devogèle et al, 2020). Moskovitz et al (2019) identified two probable near-Earth asteroid pairs 2015 EE7 -2015 FP124 (both members within the spectral taxonomic S-complex) and 2017 SN16 -2018 RY7 (both rare V-types) and they constrained their separation ages to < 10 4 yr.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, certain ancillary evidence supports the common origin scenario for this cluster, such as, highly similar spectra suggesting rare B-type taxonomic classifications for the two largest members of the cluster and the almost identical polarization properties of their surfaces (Devogèle et al, 2020). Moskovitz et al (2019) identified two probable near-Earth asteroid pairs 2015 EE7 -2015 FP124 (both members within the spectral taxonomic S-complex) and 2017 SN16 -2018 RY7 (both rare V-types) and they constrained their separation ages to < 10 4 yr.…”
Section: Introductionmentioning
confidence: 77%
“…Orbital similarity can be quantified with the Drummond D criterion (Drummond, 2000). For PR2 and QR6 D = 1.3 × 10 −4 , which is almost 30× smaller than the exceptional cases 2015 EE7 -2015 FP124 and 2017 SN16 -2018 RY7 identified by Moskovitz et al (2019). This makes them the two most similar orbits in the known near-Earth asteroid population of more than 25 000 objects (as of June 2021) according to analysis of Lowell Observatory's astorb 4 database of orbital elements.…”
Section: Object H [Mag] a [Au]mentioning
confidence: 94%
“…This pipeline has been fully vetted and been used to reduce hundreds of spectra (e.g. Devogèle et al 2019;Moskovitz et al 2019;Devogèle et al 2020). All images are first bias and flat field corrected using a series of 11 individual images to construct the master bias or flat.…”
Section: Spectroscopymentioning
confidence: 99%
“…The existence of orbital clusters in NEO space resulting from a combination of mean-motion resonances and catastrophic disruptions (rotation-or impact-induced) has been explored in the literature (see e.g. Fu et al 2005;Schunová et al 2012;de la Fuente Marcos & de la Fuente Marcos 2016b;Moskovitz et al 2019;Jopek 2020) using the available but still limited observational evidence. The dynamics of objects part of the Arjuna asteroid belt is mostly controlled by Earth, but in some cases like that of 2020 CD 3 (Bolin et al 2020;de la Fuente Marcos & de la Fuente Marcos 2020;Fedorets et al 2020), the Moon also plays a non-negligible role.…”
Section: New Earth Co-orbitalsmentioning
confidence: 99%
“…Todd et al (2012a). On the other hand, a number of NEA pairs are suspected to come from YORP-induced rotational fissions (de la Fuente Marcos & de la Fuente Marcos 2019; Moskovitz et al 2019) and Earth coorbitals may also be experiencing these processes (see e.g. de la Fuente Marcos & de la Fuente Marcos 2018a).…”
Section: Introductionmentioning
confidence: 99%